Integrated Nutrient Management on Baby Corn (Zea mays L.) - Mahapatra, A.; Barik, A. K.; Mishra, G. C. (International Journal of Bio-resource and Stress Management, 2018)
An experiment on integrated nutrient management in baby corn was carried out during kharif and rabi seasons of 2012 and 2013 at Agronomic Main Research Station of Orissa University of Agriculture and Technology, Bhubaneswar, Odisha, India. The experiment was laid out in factorial randomized block design with three replications of each twenty treatment combinations consisting of four fertility levels and five secondary and micronutrient levels. Integrated nutrient management exhibited significant effect on growth, yield attributes and yield of baby corn. Application of 75 % RDF+vermicompost @ 2.5 t ha-1+mixed bio-fertilizers recorded the highest plant height, number of leaves plant-1, LAI , dry matter accumulation of baby corn at harvest along with yield baby corn (1.50 t ha-1) and green forage (26.03 t ha-1). Application of 40 kg S ha-1+5 kg Zn ha-1+2.5 kg B ha-1 has resulted in significant increase in yield components such as number of corns plant-1, length and girth of baby corn, baby corn weight along with yield of baby corn (1.54 t ha-1) and green forage (26.17 t ha-1). The highest net return (` 77921 ha-1) and B: C ratio of 3.07 were registered in 75% RDF+vermicompost @ 2.5 t ha-1+ mixed bio-fertilizers. Application of 40 kg S ha-1+5 kg Zn ha-1+2.5 kg B ha-1 resulted in highest net return (` 81217 ha-1) and B: C ratio of 3.13.